Mathematical description of angstromtechnologies for artificial intelligence usage in aviation cybersecurity - Кузнєцова, Тетяна Вікторівна; Чирков, Артем Валерійович (Ukrainian Information Security Research Journal, 2020)
This article discusses the mathematical results in the form of a mathematical description of the management of human thought for the safety of aviation facilities based on the introduction of new author’s concepts and the author’s classification of aviation technology reform. Mathematics today faces the challenge of developing new mathematical tools to ensure cyber security in aviation. In the process of constructing a mathematical model, two systems of scientific knowledge mutually adapt - cybernetic and mathematical. With the development of information technology, this interaction has gone from the field of cybernetic research into the real practice of business management in the field of aviation. Therefore, the authors introduced new economic and mathematical concepts and determined the role of 3D-modeling in angstromtechnology of aviation enterprises from the point of view of information security and cybersecurity. The authors performed 3D-modeling of information security and cybersecurity in matters of airspace, which can be considered as a small version of the simulation usage angstrom-management technology. This work does not have the stated procedures, it requires a deep understanding of various types of neural network architectures, it includes a lot of research and analysis and can take a lot of time to prepare, but in the end it can produce the most effective solution at a certain moment and in a specific situation in a short period of time.